Heat stress memory differentially regulates the expression of nitrogen transporter genes in the filamentous red alga ‘Bangia’ sp. ESS1 - Sato, Natsumi; Khoa, Ho Viet; Mikami, Koji (Frontiers in Plant Science, 2024)
To withstand high temperatures that would be lethal to a plant in the naïve state, land plants must establish heat stress memory. The acquisition of heat stress tolerance via heat stress memory in algae has only been observed in the red alga 'Bangia' sp. ESS1. In this study, we further evaluated the intrinsic ability of this alga to establish heat stress memory by monitoring hydrogen peroxide (H2O2) production and examining the relationship between heat stress memory and the expression of genes encoding nitrogen transporters, since heat stress generally reduces nitrogen absorption. We observed a reduction in H2O2 content when heat stress memory was established in the alga. We next identified six genes encoding ammonium transporters in 'Bangia' sp. ESS1, along with a single-copy nitrate transporter gene and two urea transporter genes. Two of these nitrogen transporter genes were induced by heat stress but not by heat stress memory, two genes showed heat stress memorydependent expression, and one gene was induced by both treatments. Heat stress memory therefore differentially regulated the expression of the nitrogen transporter genes by reducing heat stressinducible gene expression and inducing heat stress memory-dependent gene expression. These findings point to the functional diversity of nitrogen transporter genes, which play different roles under various heat stress conditions. The characteristic effects of heat stress memory on the expression of individual nitrogen transporter genes might represent an indispensable strategy for reducing the threshold of sensitivity to recurrent high-temperature conditions and for maintaining nitrogen absorption under such conditions in 'Bangia' sp. ESS1.